Types of Data - Murty M Narasimha; Devi V Susheela (Introduction To Pattern Recognition And Machine Learning, 2015)
In statistical machine learning, pattern recognition and data mining, data is represented as a pattern matrix or data matrix. We illustrate it using the data in Figure 2.1 which is represented using the matrix shown in Table 2.1. Note that in Table 2.1, there are eight patterns which are represented using height in feet and weight in Kilograms. There are two classes labeled chair and human corresponding to a possible collection of chairs and humans; each class has four patterns in this example collection. Each pattern is represented as a point in the two-dimensional space, where weight is the first (X1) feature and height is the second (X2) feature.